PROSES EKSTRAKSI REAKTIF MINYAK JAHE DENGAN KATALIS HCL DENGAN BERBANTUKAN GELOMBANG ULTRASONIK - Dian Arofisma; Maharani Kusumaningrum; Abdullah Abdullah (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
The increased consumption of essential oil is mainly used in the pharmaceutical industry. One type of the essential oil is ginger oil (Zingiber officinale). The main of reaction to produce ginger oil is esterification reaction. The reaction takes place relative slowly, and it  doesn’t occur perfectly so it needs many catalyzes and alcohol.This research is expected can reduce the acid level of ginger oil and it can be obtained by the reaction of ginger oil product assisted by ultrasonic waves. The aim of this research is to obtainoptimumconditions forginger oilproductionprocesswithultrasonicwaveswhich includesa variabletemperature, catalyst concentrationto the weight ofmethanol, and theweight ratio ofmethanolbyweight ginger, to determine the most variables effect are temperature, catalyst concentrationto the weight ofmethanol, and theweight ratio ofmethanolbyweight ginger, toacquirethe characteristics ofginger oilgenerated with low acid level, and to know zingerone component in ginger oil. The research is done by ultrasonic cleaner with frequency of 40 KHz, time for reaction is 60 minutes. In this research, the variabels include the ratio of weight ginger with methanol 1:8, 1:10, 1:12, the catalyst of 2% methanol(wt),3% methanol(wt), 4% methanol(wt), And the reaction of variable temperature of 400C, 600C, 800C. The optimum variables with central composite design are the ratio of weight ginger with methanol 1:9,72;  the catalyst of 3,21 % methanol(wt), And the reaction of variable temperature of 65,920C so it has getting an optimum yield 67,09%.  highest of ginger oil conversion obtained were 64,97%, with ginger :  metanol of 1:10, catalyst of 3% and operation temperature of 60oC.